(untitled) (Innovations in Environmental Economics, 2025)
Ecological sustainability has become a major concern for emerging economies; however, evidence regarding the combined effects of financial development, technological innovation, renewable energy transition, and particularly the interaction between technological innovation and renewable energy transition remains limited for N-11 economies. To fill this gap, this study examines the impacts of financial development, technological innovation, renewable energy transition, green growth, and their interaction effect on ecological sustainability in N-11 economies during 2005-2024 using Mean Group Common Correlated Effects (MG-CCE) and Mean Group Fully Modified Ordinary Least Squares (MG-FMOLS) estimators. The results indicate that financial development, technological innovation, renewable energy transition, and green growth significantly enhance ecological sustainability. More importantly, the interaction between technological innovation and renewable energy transition is positive and significant, suggesting that innovation strengthens the environmental benefits of renewable energy adoption. Therefore, policymakers should integrate renewable energy policies with innovation-driven technological strategies to accelerate ecological sustainability and strengthen long-term environmental resilience in N-11 economies.